SPE International Symposium on Oilfield Chemistry 2015
DOI: 10.2118/173781-ms
|View full text |Cite
|
Sign up to set email alerts
|

Propagation of Carbon Nanotube Hybrids through Porous Media for Advancing Oilfield Technology

Abstract: Carbon nanotube hybrids (CNTs) have attracted research interest due to their interfacial activity. CNTs can stabilize emulsions and foams and can be used as contrast agents or tracers in rock matrix. In addition, catalytic functionalities can be attached to the nanotubes making them delivery vehicles for catalyst into zones deep inside the reservoir. Generating stable dispersion of CNTs in harsh reservoir conditions has been the main challenge for utilizing the tubes in in-situ reservoir applica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 9 publications
0
8
0
1
Order By: Relevance
“…Breakthrough curves and adsorption values suggest that the MWNT retention mechanism was similar in two columns, regardless of the presence of residual oil. In contrast, the presence of oil was observed to retain more surface‐active MWNT in the porous media because such nanoparticles preferentially adsorb at the oil/water interface (Kadhum et al, ). However, the MWNT used in our experiments were not surface active.…”
Section: Resultsmentioning
confidence: 99%
“…Breakthrough curves and adsorption values suggest that the MWNT retention mechanism was similar in two columns, regardless of the presence of residual oil. In contrast, the presence of oil was observed to retain more surface‐active MWNT in the porous media because such nanoparticles preferentially adsorb at the oil/water interface (Kadhum et al, ). However, the MWNT used in our experiments were not surface active.…”
Section: Resultsmentioning
confidence: 99%
“…Similarly, Villamizar et al [145] flooded an SWCNT-silica nanohybrid solution into a glass bed with crushed Berea sand and found that although more energy was needed for injecting the emulsion into the sand packs, the NP could effectively improve recovery through an interfacial active catalytic reaction. Kadhum et al [146] flooded MWCNT into both Berea core plugs and sand packs and saw an improved dispersion stability and propagation in high temperature and salinity conditions. The NP retention was dependent on oil saturation, with more than 80% NP found in the effluent.…”
Section: Cntmentioning
confidence: 99%
“…Было показано успешное распространение суспензий наночастиц в образцах керна (k = 200 мД). В исследовании [141] сообщается о тенденции к снижению значений межфазного натяжения и изменению смачиваемости образцов карбонатов и песчаника при использовании наногибрида SiO 2 -МУНТ без дополнительных ПАВ. Протестирована эффективность ОУНТ, МУНТ и активированного угля для создания эмульсий Пикеринга в химическом EOR [142].…”
Section: углеродные наноматериалы в Eor процессахunclassified